2016
DOI: 10.1353/hpu.2016.0133
|View full text |Cite
|
Sign up to set email alerts
|

Health Literacy and Education as Mediators of Racial Disparities in Patient Activation Within an Elderly Patient Cohort

Abstract: The Patient Activation Measure (PAM) assesses facets of patient engagement to identify proactive health behaviors and is an important predictor of health outcomes. Health literacy and education are also important for patient participation and successful navigation of the health care system. Because health literacy, education and patient activation are associated with racial disparities, we sought to investigate whether health literacy and education would mediate racial differences in patient activation. Partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
33
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 49 publications
2
33
1
Order By: Relevance
“…Additionally, although we did not assess health literacy, in prior evaluations of internal medicine and geriatric populations, the relationship between race and patient activation was significantly mediated by education and health literacy. 38,39 Our study was large, including a cohort of patients with self-reported UC or CD and careful methodology that has been utilized in numerous other studies within IBD Partners. 17-19, 28, 29 However, our study also has limitations.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, although we did not assess health literacy, in prior evaluations of internal medicine and geriatric populations, the relationship between race and patient activation was significantly mediated by education and health literacy. 38,39 Our study was large, including a cohort of patients with self-reported UC or CD and careful methodology that has been utilized in numerous other studies within IBD Partners. 17-19, 28, 29 However, our study also has limitations.…”
Section: Discussionmentioning
confidence: 99%
“…Participants also expressed support for the ideas that patient involvement and high levels of health literacy are necessary in illness management and that knowledge is needed to guarantee patient involvement (Liu et al., ). These may be important precursors to improved preventative and therapeutic self‐management behaviour (Eneanya et al., ). Supporting these findings, prior studies have found that though the level of people's education may not rise as they get older, their health literacy may improve due to social interactions and meetings with professionals (Bostock & Steptoe, ; Tennant et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…16 Enhancing patient activation and self-care by strengthening therapeutic alliance could be an important strategy to mitigate racial/ethnic disparities in hemodialysis treatment adherence and improve overall outcomes for patients with ESKD. 17 Despite the substantial evidence of reduced hemodialysis treatment adherence among Blacks, no report to our knowledge has systematically reviewed the hemodialysis treatmentadherence literature specifically on Blacks to garner input that will inform clinical practice and research. Nor do there appear to be any reports that have undertaken an assessment of the application of theoretical frameworks or the inclusion of therapeutic alliance to enhance the success of interventions targeting improvement in hemodialysis treatment adherence.…”
Section: Introductionmentioning
confidence: 99%